Party Politics in West Bengal: Historical and Contemporary Dynamics - Hussain, Md. Iftekhar; Mir, Aijaz Ahmad (Integrated Journal for Research in Arts and Humanities, 2024)
Party politics in West Bengal is a complex and ever-evolving phenomenon deeply rooted in the state's socio-cultural history. This overview explores the dynamic landscape of party politics in West Bengal, tracing its historical evolution and examining the key players, ideological underpinnings, electoral strategies, and socio-economic factors that have influenced voter preferences over the years. From the pre-independence era's freedom struggle to the contemporary political dynamics dominated by the All-India Trinamool Congress (AITC) and Bharatiya Janata Party (BJP), West Bengal's political journey reflects its vibrant cultural mosaic and socio-political complexities. This paper also discusses the current scenario in West Bengal, highlighting the role of various political parties in recent local and assembly elections. The methodology involves a comprehensive review of academic papers and journals on various aspects of West Bengal's politics, governance, and societal dynamics. While existing literature touches on governance-related aspects like healthcare policies, decentralisation, and power sector reforms, there is a research gap in integrating these elements to provide a holistic assessment of West Bengal's governance model. The paper identifies this research gap and calls for a more comprehensive study that explores the interplay of political decisions, decentralisation efforts, and policy reforms in shaping the state's development and governance outcomes.